Large left moiety renal tumor with renal vein thrombus in a horseshoe kidney - Abhishek Bhat; Bruce Kava (African Journal of Urology, 2022)
Abstract Background Management of large renal tumors in a horseshoe kidney has received little attention due to the highly infrequent occurrence. Surgical management for tumors in horseshoe kidney is challenging due to complex aberrant vascular anatomy, relative fixity of the renal moieties and other associated conditions such as ectopia and malrotation. An added component of a renal vein thrombus in this scenario often adds to the surgical conundrum. Inadequate peri-operative management may cause devastating complications and increased morbidity and mortality. Careful pre-operative planning and meticulous intra-operative dissection limits blood loss and thereby complications. Case presentation We present the peri-operative management of a large renal tumor with a renal vein thrombus in a horseshoe kidney moiety as a case report with literature review focusing on the intra-operative surgical approach that may be adopted for these tumors. A 12 cm × 10 cm left renal moiety mass with renal vein thrombus with no distant metastasis was diagnosed. After confirmation of thrombus extent with CT as well as MRI Abdomen, the patient underwent left moiety radical nephrectomy with renal vein thrombectomy. Careful intra-operative dissection and division of the vascular supply of the left renal moiety was performed. Vessel stapler was used for division of isthmus that resulted in minimal blood loss, complete oncologic clearance and minimal post operative morbidity. Conclusions Large renal tumor with renal vein thrombus in horseshoe kidneys is an uncommon condition. Pre operative cross-sectional imaging and intra-operative use of vessel sealants like Ligasure, harmonic scalpel and vessel staplers contribute to minimizing blood loss and thereby result in excellent patient outcomes. We report a case of a large left renal moiety tumor with renal vein thrombus successfully managed with open radical left moiety nephrectomy and isthmectomy with tumor thrombectomy.